2011
DOI: 10.1088/2041-8205/734/1/l18
|View full text |Cite|
|
Sign up to set email alerts
|

Convective Nature of Sunspot Penumbral Filaments: Discovery of Downflows in the Deep Photosphere

Abstract: We study the velocity structure of penumbral filaments in the deep photosphere to obtain direct evidence for the convective nature of sunspot penumbrae. A sunspot was observed at high spatial resolution with the 1-m Swedish Solar Telescope in the deep photospheric C i 5380 Å absorption line. The Multi-Object Multi-Frame Blind Deconvolution (MOMFBD) method is used for image restoration and straylight is filtered out. We report here the discovery of clear redshifts in the C i 5380 Å line at multiple locations in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 30 publications
6
53
1
Order By: Relevance
“…As a consequence, magnetic field with inverse polarity and downflow velocities should be observed all along the boundaries of bright penumbral filaments. While observational evidence for convective downflows in the whole penumbra has been recently reported (Scharmer et al 2011;Scharmer & Henriques 2012;Joshi et al 2011), the reversed flux has only been observed in the outer penumbra (Westendorp Plaza et al 1997del Toro Iniesta et al 2001). But even with the highest spatial resolution spectropolarimetry, we have been unable to observe them in the inner penumbra (Langhans et al 2005).…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…As a consequence, magnetic field with inverse polarity and downflow velocities should be observed all along the boundaries of bright penumbral filaments. While observational evidence for convective downflows in the whole penumbra has been recently reported (Scharmer et al 2011;Scharmer & Henriques 2012;Joshi et al 2011), the reversed flux has only been observed in the outer penumbra (Westendorp Plaza et al 1997del Toro Iniesta et al 2001). But even with the highest spatial resolution spectropolarimetry, we have been unable to observe them in the inner penumbra (Langhans et al 2005).…”
Section: Introductionmentioning
confidence: 52%
“…We can assess that our inverse profiles do not come from such an artificial effect for two reasons. First, we have undercorrected our data, because the used PSF is a lower limit of the real one (see, for instance, Joshi et al 2011). As a consequence, the continuum contrast has only changed from 6.3% in the original data to 11.8% in the deconvolved data.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the claims of Franz & Schlichenmaier (2009 and Puschmann et al (2010a), the presence of downflows in the inner penumbra has been reported by Sánchez Almeida et al (2007), Joshi et al (2011), Scharmer et al (2011) and Scharmer & Henriques (2012 1 . In a recent study, Scharmer et al (2013) report narrow downflow lanes to be located at the boundaries between spines and inter-spines.…”
Section: Structure Of Penumbral Filamentsmentioning
confidence: 64%
“…Indirect support for azimuthal convection was put forward by Ichimoto et al (2007a), Zakharov et al (2008), Spruit et al (2010), Bharti et al (2010), although an alternative explanation of some of these observations in terms of waves has also been provided (Bharti et al 2012). Recent observations from the Swedish Solar Telescope (SST: Scharmer et al 2003)/CRisp Imaging Spectro-Polarimeter (CRISP) showed downflows in the inner penumbra and a qualitative association of upflows with hot and downflows with cool gas in the deep photosphere (Joshi et al 2011;Scharmer et al 2011;Scharmer & Henriques 2012). A&A 557, A25 (2013) However, some other researchers did not detect such flow patterns (Franz & Schlichenmaier 2009;Bellot Rubio et al 2010;Puschmann et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been confirmed that the Evershed flow can reach supersonic and super-Alvénic values, not only on the outer penumbra (Borrero et al 2005;van Noort et al 2013), but also close to the umbra (del Toro Iniesta et al 2001;Bellot Rubio et al 2004) and has a strong upflowing component at the inner penumbra that turns into a downflowing component at larger radial distances (Franz & Schlichenmaier 2009Tiwari et al 2013). Finally, there is strong evidence for an additional component of the velocity field in intraspines that appears as convective upflows along the center of the intraspines that turns into downflows at the filaments' edges (Zakharov et al 2008;Joshi et al 2011;Scharmer et al 2011;Tiwari et al 2013). These downflows seem capable of dragging the magnetic field lines and turning them back into the solar surface (Ruiz Cobo & Asensio Ramos 2013;Scharmer et al 2013).…”
Section: Introductionmentioning
confidence: 99%